Sistem Pendukung Media Pembelajaran Menggunakan Chatbot dan LINE Pada PKBM Berdaya Indonesia - Dina Fitria Murad; Daffa Fauzan Basukiputra; Michael Hendra Wijaya; M Iqbal Fauzi (ULTIMA InfoSys, 2019)
The purpose of this study was to develop a learning model by utilizing chatbot technology that was integrated with LINE's chat media for the Indonesian C-based PKBM package C program. The learning model that was built functioned as a support system for learning media to independently learn access to learning materials, discussion and work on the questions and discussion of National Examination exercises distributed from a content management system (CMS) through a program. The research method is composed using the Systems Development Life Cycle (SDLC). The analysis is done by identifying the problems of the learning system business processes that are running. The results of this study are chatbot-based learning models that are integrated with the LINE chat application which contains the distribution of material, practice questions, discussion to an evaluation of student learning that will help the teaching and learning system in Indonesian-powered PKBM